2002
DOI: 10.1128/aac.46.6.1953-1959.2002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Antifungal Therapy in a Nonneutropenic Murine Model of Zygomycosis

Abstract: Three isolates of zygomycetes belonging to three different genera (Rhizopus microsporus, Absidia corymbifera, and Apophysomyces elegans) were used to produce a disseminated infection in nonimmunocompromised mice. The therapeutic efficacy of amphotericin B, given intraperitoneally at doses ranging from 0.5 to 4.5 mg/kg of body weight/day, oral itraconazole at 100 mg/kg/day, and oral terbinafine at 150 mg/kg/day was evaluated in this model. The markers of antifungal efficacy were the median survival time, the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
2
36
1
Order By: Relevance
“…Apophysomyces elegans infection rapidly progresses to necrosis, typically within days after inoculation, which may be explained by rapid growth of the organism in blood vessels (56 (279). However, one study indicated that a 250-to 2,300-fold lower inoculum of Apophysomyces elegans spores was required to cause equivalent mortality in animals compared to those for Rhizopus microsporus and Lichtheimia corymbifera (74,77). (36, 64, 117a, 246, 275, 298, 363).…”
Section: Apophysomyces Elegans Complexmentioning
confidence: 99%
“…Apophysomyces elegans infection rapidly progresses to necrosis, typically within days after inoculation, which may be explained by rapid growth of the organism in blood vessels (56 (279). However, one study indicated that a 250-to 2,300-fold lower inoculum of Apophysomyces elegans spores was required to cause equivalent mortality in animals compared to those for Rhizopus microsporus and Lichtheimia corymbifera (74,77). (36, 64, 117a, 246, 275, 298, 363).…”
Section: Apophysomyces Elegans Complexmentioning
confidence: 99%
“…20,81 In an experimental model, itraconazole reduced mortality of immunocompetent mice infected with Lichtheimia corymbifera and Apophysomyces elegans but not in animals infected with Rhizopus microspores. 82 Despite rare case reports, [83][84][85][86] data are insufficient to support its use as monotherapy for mucormycosis in clinical practice.…”
Section: Other Azolesmentioning
confidence: 99%
“…To obtain infected tissue samples, an animal model of disseminated zygomycosis in nonimmunosuppressed mice was used. In this model, the two main target organs are the brain and kidneys (8). Female specific-pathogen-free outbred OF1 mice (age, 7 weeks; weight, 22 to 24 g; Charles River Laboratories, L'Arbresle, France) were used for the experiments.…”
mentioning
confidence: 99%
“…The section starting each series of slide cuts prepared for each laboratory was microscopically examined after it was stained with Gomorimethenamine silver (GMS) to confirm the presence of hyphae. Quantification of the fungal burden in the organs before fixation was not attempted, as it has been demonstrated that determination of the numbers of CFU for Zygomycetes is not a reliable marker of infection in this model (8). The organs from uninfected mice were processed similarly and were used as negative controls.…”
mentioning
confidence: 99%
See 1 more Smart Citation